“Developing Students’ Problem-Solving Abilities Through Project-Based Extracurricular Activities” - Djabbarova Nargiza Bakitovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of project-based extracurricular activities in enhancing students’ problem-solving abilities. It emphasizes how collaborative projects, hands-on tasks, and digital tools can improve analytical thinking, creativity, and independent learning. The study also highlights effective pedagogical strategies for maximizing engagement and skill development in extracurricular programs.